Seasonal cycle of plankton production in the Iberian margin based on a high resolution ocean model - Reboreda, Rosa
The seasonal variability of plankton in the entire Iberian margin and the adjacent oceanic region was simulated by applying a NPZD-type biogeochemical model coupled to a physical high resolution configuration of the 3D Regional Ocean Modeling System (ROMS). The NPZD model simulated the time and space evolution of nitrate, phytoplankton/chlorophyll, zooplankton and detritus. Model results were compared to remotely sensed sea surface temperature from AVHRR, mixed layer depth from ARGO floats, and sea surface chlorophyll-a from a monthly SeaWiFS climatology. The model was able to reasonably reproduce the seasonal cycle of phytoplankton biomass in the Iberian Atlantic margin and the adjacent oceanic region. It allowed us to make a general characterization of the spatio-temporal patterns of phytoplankton and zooplankton biomass, as well as detritus and nitrate distribution. However, some limitations in the model were revealed by the Taylor Diagrams analysis. The model seemed to overestimate the offshore spring phytoplankton bloom and the upwelling-related coastal maxima of chlorophyll-a in the shelf. On the other hand, winter chlorophyll-a decrease simulated by the model over the shelf agreed with in situ samplings reported in the literature, contrasting with the high chlorophyll-a estimations of satellite data. This evidenced that care should be taken when validating model results in the Iberian coastal region using satellite chlorophyll-a products, particularly in winter.